The Reflection of self competency of the managers in their behavior - الزيدي ناظم جواد; حسين حسين وليد (Journal of Economics and Administrative Sciences, 2018)
Abstract This research aims to measure the effect of Self competency of the Managers in their behavior from the view point of the working individual in the organization since the behavior of managers is considered to be one of the essential variables in the organization which can affect the performance and the commitment of the working individual. the questioners was used to gather the data and the Iraqi Rail Road co. was the field of the study . and a random sample of (36) individual of the subordinates of the managers society of the study and used the (SPSS) statistical program was used in the analysis of the data of the research . the findings refer to the existence of a clear effect for the Self competency in their behavior toward their subordinates , therefore the research condoled that there is an audience for effective relationship between the self competency of the manager in their competency and their behavior therefore the research recommended for the necessity for increasing the cancers on the organization in studying the subject related to the managers which are represented in their perditions and behavior and the most influential variables becomes because of their great effects in the process of motivating the employees and increasing their driver in the job and improving the manner of human resources in the organization.